Internet-based corporate disclosure and market value : evidence from Latin America (2013)
We examine the relationship between an Internet-based corporate disclosure index and firm value in the seven largest stock markets of Latin America. We find, after controlling for firms' characteristics, industry and country of origin, that an increase of 1% in the Internet-Based Corporate Disclosure Index causes an increase of 0.1592% in the Tobin's Q and an increase of 0.0119% in the firm's ROA. These findings are robust after considering the potential endogeneity of our regression variables. The evidence contributes to the literature suggesting that firms can differentiate themselves by self-adopting better financial and corporate disclosure measures using the Internet.